Clinical applicability of real-time, prehospital image transmission for FAST (Focused Assessment with Sonography for Trauma). (December 2013) - Song, Kyoung Jun; Shin, Sang Do; Hong, Ki Jeong; Cheon, Kyoung Woo; Shin, Ilhyoung; Song, Sung-Wook; Kim, Hee Chan
We evaluated a real-time, prehospital ultrasound image transmission system for use in focused assessment with sonography for trauma (FAST). The wireless, real-time ultrasound image transmission system comprised an ultrasound scanner with a convex abdominal transducer and a notebook computer connected to a 3 G wireless network for video data transmission. In our simulation experiment, ultrasonography was performed by emergency medical technicians (EMTs) on a human body phantom with simulated haemoperitoneum. Transmitted ultrasound video clips were randomly rearranged and presented to emergency physicians to make a diagnosis of haemoperitoneum. A total of 21 ultrasound video clips was used and 13 emergency physicians participated in the study. The sensitivity and specificity were 90.0% (95% Confidence Interval, CI, 83.5–94.6) and 85.3% (95% CI 78.4–90.7) respectively, and the accuracy of detecting abnormal ultrasound results was 87.7% (95% CI 83.8–91.6). Diagnosis of hemoperitonuem in trauma patients by an emergency physician based on the transmitted video images of FAST performed by an EMT is feasible, and has an accuracy of about 88%.